Helping women transition out of sex work: study protocol of a mixed-methods process and outcome evaluation of a sex work exiting program - Martine Shareck; Pearl Buhariwala; Maha Hassan; Patricia O'Campo (BMC, 2020)
Abstract Background For women who want to, exiting sex work can be challenging. Numerous programs strive to help women wanting to exit sex work and secure alternative sources of income by providing targeted support at key moments during the transition, yet few of those initiatives are rigorously evaluated. In 2017 "Exit Doors Here", a 9-month sex work exiting program based on the critical time intervention (CTI) approach, was developed to provide wrap-around support services (e.g., health, addiction, housing, education, and employment supports) to women wishing to transition towards exiting sex work. Methods We present the design of an evaluation study of Exit Doors Here which combines quantitative and qualitative methods to assess participant recruitment and retention into the program, program fidelity, and relationships with service providers (process evaluation), as well as progress made by participants in terms of strengthening their social support networks and moving closer to achieving their housing, pre-employment (i.e., educational, training and volunteering), and income-related goals, as well as their involvement in sex work (outcome evaluation). Each year for 4 years, between 25 and 30 Exit Doors Here clients will be invited to complete an interviewer-administered questionnaire at the beginning and after completing the program, and to share data from their CTI charts and related documentation. Once a year, program staff and peer workers will be interviewed, and service providers will be surveyed. Discussion Conducting a formative (process) evaluation will allow us to inform program implementation and improve program delivery early on for maximum benefit. The summative (outcome) evaluation will provide much needed evidence on the effectiveness of CTI in supporting a traditionally underserved population to achieve the housing, pre-employment and income-related goals they value, and their progress towards reducing their involvement in, and eventually exiting, sex work.